(untitled) - Distenfield, Ira (Hoboken, N.J., 2005)
We The People's Guide to Divorce makes filing for divorce as affordable and painless as possible. This practical, nuts-and-bolts guide covers all the basics and includes extra resources you'll be glad you had--including frequently asked questions, sample forms, a glossary of legal terms, and handy worksheets. Plus, when you purchase We The People's Guide to Divorce, you'll be able to download legal forms to complete your divorce filing.
Keywords: Divorce; Law and legislation,Popular works; United States